Engineering of nanoparticle size via electrohydrodynamic jetting. Issue 1 (20th June 2016) - Rahmani, Sahar; Ashraf, Sumaira; Hartmann, Raimo; Dishman, Acacia F.; Zyuzin, Mikhail V.; Yu, Chris K. J.; Parak, Wolfgang J.; Lahann, Joerg
Abstract: Engineering the physical properties of particles, especially their size, is an important parameter in the fabrication of successful carrier systems for the delivery of therapeutics. Here, various routes were explored for the fabrication of particles in the nanosize regime. It was demonstrated that the use of a charged species and/or solvent with high dielectric constant can influence the size and distribution of particles, with the charged species having a greater effect on the size of the particles and the solvent a greater effect on the distribution of the particles. In addition to the fabrication of nanoparticles, their fractionation into specific size ranges using centrifugation was also investigated. The in vitro particle uptake and intracellular transport of these nanoparticles was studied as a function of size and incubation period. The highest level of intralysosomal localization was observed for the smallest nanoparticle group (average of 174 nm), followed by the groups with increasing sizes (averages of 378 and 575 nm), most likely due to the faster endosomal uptake of smaller particles. In addition, the internalization of nanoparticle clusters and number of nanoparticles per cell increased with longer incubation periods. This work establishes a technological approach to compartmentalized nanoparticles with defined sizes. This is especially important as relatively subtle differences in size can modulate cell uptake and determine intercellular fate. Future work will need to address the role of specific targeting ligands on cellular uptake and intracellular transport of compartmentalized nanoparticles. Abstract : Engineering of nanoparticle size is an important parameter in the fabrication of carriers for drug delivery applications. Here, nanoparticles are fabricated using the electrohydrodynamic jetting technique using various methods (concentrations, solvents, and charged species) and are further isolated into specific size ranges using serial centrifugation. The uptake of nanoparticles as a function of size is investigated using HeLa cells.